Resistant Ventricular Arrhythmia and the Role of Overdrive Pacing in the Suppression of the Electrical Storm - Mohamed Magdi; Mahmood Mubasher; Hakam Alzaeem; Tahir Hamid (Case Reports in Cardiology)
Ventricular arrhythmia storm is a state of cardiac instability characterized by multiple ventricular arrhythmias or multiple ICD therapies within a 24-hour duration. Management of this life-threatening state depends on the reversal of the cause besides either electrical or medical management of the arrhythmia. We report a case of a 54-year-old male who underwent a percutaneous coronary intervention following massive acute myocardial infarction. Afterwards, he developed frequent life-threatening ventricular arrhythmias that required multiple shocks and antiarrhythmic medications. Despite all these interventions, it was very difficult to control the electrical instability, but after overdrive ventricular pacing, the storm subsided and within a few days the case was stabilized. Overdrive pacing is an easy temporary modality to control the resistant arrhythmia following myocardial infarction.